New Interactive Method for Solving Multiobjective Linear Programming Problems - Kanaya , Ziad; Dribate , Mouhamed; Nasser , Waeel (Latakia University Journal -Basic Sciences Series, 2018)
In this paper we offer a new interactive method for solving Multiobjective linear programming problems. This method depends on forming the model for reducing the relative deviations of objective functions from their ideal standard, and dealing with the unsatisfying deviations of objective functions by reacting with decision maker. The results obtained from using this method were compared with many interactive methods as (STEM Method[6] – Improvement STEM Method[7] – Matejas-peric Method[8]). Numerical results indicate that the efficiency of purposed method comparing with the obtained results by using that methods at initial solution point and the other interactive points with decision maker.